Original Sin and Procylical Fiscal Policy : Two Sides of the Same Coin? - Adler, Gustavo (IMF Working Papers; Working Paper ;, 2008)
The paper develops a simple model of sovereign debt where default both through direct repudiation and through inflation are possible and give rise to (endogenous) constraints on the currency composition and the level of public debt. This set up allows to show that procyclicality of fiscal policy in EMEs can arise as a by-product of the "original sin" and both can be explained by the presence of weak monetary institutions which cannot commit to price stability. The paper suggests that, as monetary institutions in EMEs strengthen, the "original sin" would fade away and the cyclical properties of fiscal policy would improve.